Advertising arbitrage - Sergei Kovbasyuk; Marco Pagano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Speculators often advertise arbitrage opportunities in order to persuade other investors and thus accelerate the correction of mispricing. We show that in order to minimize the risk and the cost of arbitrage an investor who identifies several mispriced assets optimally advertises only one of them, and overweights it in his portfolio; a risk-neutral arbitrageur invests only in this asset. The choice of the asset to be advertised depends not only on mispricing but also on its "advertisability" and accuracy of future news about it. When several arbitrageurs identify the same arbitrage opportunities, their decisions are strategic complements: they invest in the same asset and advertise it. Then, multiple equilibria may arise, some of which inefficient: arbitrageurs may correct small mispricings while failing to eliminate large ones. Finally, prices react more strongly to the ads of arbitrageurs with a successful track record, and reputation-building induces high-skill arbitrageurs to advertise more than others.
urn:nbn:de:hebis:30:3-351249
Keywords: G11; G14; G2; D84; 330; limits to arbitrage; advertising; price discovery; limited attention